A Review of Global Optimization Methods for Molecular Structures Algorithms, Applications and Perspectives - Alvarez, Jorge Alberto Sanchez (Journal of computational chemistry, 2025)
© 2025 The Author(s). Journal of Computational Chemistry published by Wiley Periodicals LLC.